A Gender-Based Linguistic Patterns in Quora Apps: A Comparative Study - Candra Dewi, Tinara; Widyawati, Wiwin; Rochmahwati, Pryla; Khasanah, Nurul (SALEE: Study of Applied Linguistics and English Education, 2024)
There is a wide variety of interrelated social media platforms. Gender orientation can affect preferences for language use in particular social media, especially Quora, which is famous as a medium for collecting questions and answers on specific topics. Breaking new ground, this study uniquely juxtaposes gender orientation with linguistic preferences on Quora, an unexplored research area. This content analysis design employed textual data posted by Quora users in the "Skilled English Writing" forum during January-March 2023. Following Lakoff's gendered language theory, women frequently employ hedges to indicate uncertainty, whereas men use boosters to express confidence. The language of women was characterized by greater formality and formal grammar, whereas men favored informal abbreviations. In addition, women utilized emoticons for emphasis more frequently than males. These linguistic differences result from complex social, cultural, biological, and psychological effects, underscoring the importance of gender and social factors in language formation.